The Institutional Staging of an Examination - Albas, Daniel; Albas, Cheryl (Canadian Journal of Higher Education, 1988)
This study employs the dramaturgical approach to the staging of examinations. In focusing on the staging we attempt to convey the university definition of the exam as well as the means by which institutionally desired moods and actions are communicated to students. Through the use of space, props, equipment, and human actors the university stresses the larger societal values of universalism and individual achievement. In so doing the university develops a "rhetoric of idealization" to compensate for the inevitable discrepancies in fairness and equality of treatment.